Estudio de prefactibilidad para la implementación de una planta de generación de energía eléctrica a base de biogás producido por la descomposición de los residuos sólidos orgánicos - Gil Lozano, Gian Franco (2022)
This project involves the development of an electricity generation plant based on biogas produced by the decomposition of organic waste located in Metropolitan Lima. This project is attractive because the state is constantly promoting the development of Renewable Energy Resources (RER) through favorable legislation. The aim is to give it a greater participation in the topic of clean energies in the energy matrix. The entity OSINERGMIN has been conducting energy bidding auctions for a period of 20 years since 2010. In order to asses the feasibility of the present project it is necessary to carry out several studies, which are composed by chapters. Chapter 1 explains the general aspects of the research. In addition, the problem, the specific and general objectives. Chapter 2 explains the aspects of the market study, it is worth mentioning that our only client is the Peruvian government. In chapter 3, we analyzed the most appropriate location for our plant. In chapter 4, the analysis of the selection of the size of the plant was carried out, which was influenced by various factors such as technology, investment, market, and the amount of organic waste needed to generate electricity. In chapter 5, we described the engineering description of the project, in which we describe the service we will provide, the processes involved and the existing technologies. In chapter 6, we explain the business organization, the number of workers we will have in our plant, board of directors, administrative and service personnel, and their corresponding functions. Chapter 7 explains both the economic and financial aspects. In addition, we will demonstrate by means of the NPV, IRR and B/C indicators the reason why our project would be profitable. In chapter 8, the analysis of the social evaluation is carried out, which includes the social indicators and the interpretation of the value of the result of each one.